Perjanjian Pra-Nikah Perspektif Islam: Studi Fenomenologi di Era Society 5.0 - Sofyan, Aa (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2023)
This article examines the urgency of prenuptial agreements in the context of Society 5.0,characterized by digital transformation and technological integration. Prenuptialagreements are seen as an important instrument for regulating marital relationships fairlyand transparently, in line with modern values such as gender equality and justice. In theSociety 5.0 era, prenuptial agreements can be utilized efficiently and easily accessed. Thestudy also identifies the potential negative impacts of prenuptial agreements, includingpower imbalances between partners, reduced fairness in the division of joint assets,difficulties in revoking agreements, potential tension in marital relationships, and negativeimpacts on children, highlighting the need for a balance between the benefits and risks ofprenuptial agreements in the context of an increasingly complex and diverse modernsociety. This research employs a qualitative approach with data analysis involving literaturereviews and case studies. The findings of this article suggest that prenuptial agreements inthe Society 5.0 era can serve as a basis for wiser policies in regulating marital relationshipsin the future.